2016
DOI: 10.1364/ao.55.006644
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity optical waveguide accelerometer based on Fano resonance

Abstract: An optical waveguide accelerometer based on tunable asymmetrical Fano resonance in a ring-resonator-coupled Mach-Zehnder interferometer (MZI) is proposed and analyzed. A Fano resonance accelerometer has a relatively large workspace of coupling coefficients with high sensitivity, which has potential application in inertial navigation, missile guidance, and attitude control of satellites. Due to the interference between a high-Q resonance pathway and a coherent background pathway, a steep asymmetric line shape i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Referring to the application of polymers in accelerometers, in [ 20 ], an SU-8-polymer-based, single-mass, three-axis, piezoresistive accelerometer was built ( Figure 2 a); it demonstrated better sensitivity due to the low Young’s modulus of SU-8 compared with Si, and piezoresistive materials such as ZnO nanorods were employed as sensing materials applied on the surface of U-beams to detect deformation. In [ 21 ], a polymeric Fano-resonator-based accelerometer was fabricated ( Figure 2 b); when being accelerated, a force was exerted on the ring, which experienced a strain, causing a phase change of the light proportional to the acceleration. This device demonstrated very high sensitivity.…”
Section: Sensors and Sensor-based Odometry Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to the application of polymers in accelerometers, in [ 20 ], an SU-8-polymer-based, single-mass, three-axis, piezoresistive accelerometer was built ( Figure 2 a); it demonstrated better sensitivity due to the low Young’s modulus of SU-8 compared with Si, and piezoresistive materials such as ZnO nanorods were employed as sensing materials applied on the surface of U-beams to detect deformation. In [ 21 ], a polymeric Fano-resonator-based accelerometer was fabricated ( Figure 2 b); when being accelerated, a force was exerted on the ring, which experienced a strain, causing a phase change of the light proportional to the acceleration. This device demonstrated very high sensitivity.…”
Section: Sensors and Sensor-based Odometry Methodsmentioning
confidence: 99%
“…Copyright IEEE 2019. ( b ) Polymeric Fano-resonator-based accelerometer, reprinted with permission from [ 21 ].Copyright The Optical Society2016. ( c ) Polymeric vibratory ring-type MEMS gyroscope, reprinted with permission from [ 27 ].…”
Section: Sensors and Sensor-based Odometry Methodsmentioning
confidence: 99%
“…As depicted in Fig. 7(a), the total coupling efficiency remains almost constant regardless of the variations in WEWG, which can be used for applications based on wide waveguides like gyroscopes and accelerometers [37], [38]. Notably, the end of the taper tip is elongated for improving the cleaving tolerance, and the length of the tip waveguide (LTWG) negligibly affects the performance, as shown in Fig.…”
Section: Fabrication and Characterization Of The Proposed Couplermentioning
confidence: 97%
“…Yu Chen et al demonstrated that flexible photonic devices have been manufactured onto flexible substrates without compromising their function and performance [ 26 ]. Moreover, when combining the mechanical flexibility and excellent optical performance, the flexible optical micro-resonators have great potential for applications in optical ultrasonic sensor [ 27 , 28 ], optical accelerometer [ 29 , 30 ], optical strain sensor [ 31 , 32 ] and optical temperature sensor [ 33 , 34 ]. However, the sensing performance of flexible photonic resonators will be seriously damaged in the biochemical sensing application due to the non-biological impact on the device when experiencing mechanical deformation.…”
Section: Introductionmentioning
confidence: 99%